Current Developments and Best Practice in Open and Distance Learning - Rocha Trindade, Armando; Carmo, Hermano; Bidarra, José (International Review of Research in Open and Distributed Learning, 2000)
Through the many documents regularly emitted by those dedicated to this activity, it is comparatively easy to describe factual developments in the field of open and distance education in different places in the world. However, it is much more difficult to produce judgements of value about their quality. Quality is a subjective rather than an absolute concept and may be examined from different analytical perspectives: consumers' satisfaction level, intrinsic value of scientific and technical content of learning materials, soundness of learning strategies, efficiency of organisation and procedures, adequate use of advanced technologies, reliability of student support mechanisms, etc. These parameters should be put into the context of specific objectives, nature of target populations and availability of different kinds of resources. In a specific geographic, social, economic and cultural situation a given set of solutions might be judged as adequate and deserving the qualification of "good practice", while in a different context it could be considered of rather poor quality. The selection of examples in this article is the sole responsibility of the authors: neither should the chosen cases be considered as clearly better than any other one, nor missing cases be interpreted as lack of appreciation or a negative judgement. Finally, the authors are aware of the risks of interpreting trends and trying to extrapolate them into the near future: readers should use their own judgement in accepting (or forcefully rejecting) these projections.